Determining a National Trauma Prognostic Scale (TPS) to Predict Preventable Trauma Death in Iran: the Research Protocol - Jalilvand, Hadi; Sadeghi-Bazargani , Homayoun; Nouri Sari , Hassan; Meshkin , Mohammad; Kolivand, Pir-Hossein; Ala , Alireza; Pourasghar, Faramarz; Ojaghi Haghighi 2, Seyyed Hossein; Asghari Jafarabadi 2, Mohammad; Rahmani , Farzad; Salamati , Peyman; Deljavan Anvari , Reza; et al. (Shahroud Journal of Medical Sciences, 2021)
Methods: A 7-phases methodology will be applied to conduct this study as following; 1- Identification of trauma severity parameters and scales predicting mortality from literature, 2- Developing a data collection tool for research data collection), 3- Data collection in selected clinical settings, 4- Statistical modeling, 5- Model adaptation with three levels of trauma care settings including pre-hospitals, general hospitals and trauma specialty hospitals, 6- Scale-up and extrapolation, and 7- comparison with international models and selection of Iranian national model.Results: The content validity of the tool was confirmed with a total scale-level content validity (S-CVI) = 0.93. The reliability of the final instrument was calculated using the Pearson correlation coefficient and the Spearman correlation was evaluated above 0.7 for all cases. Up to date April 2020, From the hospital of the study, 210 patients participated in the study. The mean and standard age deviation of patients was 35.18 ± 18.44 and 165 (78.57 %) of these patients were male. The most important cause of trauma in patients was a motorcycle accident (27.62 %).Keywords: Trauma, Modeling, Injury severity assessment, Mortality predictor, Trauma scale